Políticas públicas baseadas em evidências (PPBEs): Delimitando o problema conceitual - Maurício Mota Saboya Pinheiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This paper aims to make a conceptual analysis of what can be understood as evidences in the so-called evidence-based policymaking (EBP) approach. It proposes a general method of analysis inspired by the mature work of the Austrian philosopher Ludwig Wittgenstein, who does not seek logically precise definitions. It is assumed that the concept of evidence is irremediably vague, imprecise and multidimensional, which does not mean its impossibility of elucidation, nor its futility for the analysis of public policies. Therefore, the paper tries to clarify the concept gradually, which involves the following steps: consideration of the history of EBP, articulation of their epistemological assumptions, and a panoramic view of the "conceptual terrain" of the evidence, with emphasis on their contexts of use. Finally, the work provides a set of guidelines conceptual, methodological and theoretical in character -, capable of assisting future applied research efforts in this theme.
Keywords: B40; Z18; 330; public policy; evidence-based public policy; conceptual analysis